2017
DOI: 10.1186/s12898-017-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and abiotic drivers of intraspecific trait variation within plant populations of three herbaceous plant species along a latitudinal gradient

Abstract: BackgroundThe importance of intraspecific trait variation (ITV) is increasingly acknowledged among plant ecologists. However, our understanding of what drives ITV between individual plants (ITVBI) at the population level is still limited. Contrasting theoretical hypotheses state that ITVBI can be either suppressed (stress-reduced plasticity hypothesis) or enhanced (stress-induced variability hypothesis) under high abiotic stress. Similarly, other hypotheses predict either suppressed (niche packing hypothesis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 65 publications
3
46
0
1
Order By: Relevance
“…Plant community theories predict that increasing light availability can modulate the herb layer development trajectory in sites where N and P are less limiting to plant growth (Grime, ; Jabot & Pottier, ; Tilman, ), which has been observed in temperate forest understories (Baeten et al, ; Hedwall & Brunet, ). Second, this increase in light availability can accelerate effects of climate warming so that herbaceous communities come to resemble those of warmth‐adapted communities (Bjorkman et al, ; De Frenne et al, ; Helsen et al, ; Henn et al, ; Hoeppner & Dukes, ). The increasing light availability may also alter soil microbial communities and enhance their activity which can release nutrients for plants (Ma et al, ; Ni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant community theories predict that increasing light availability can modulate the herb layer development trajectory in sites where N and P are less limiting to plant growth (Grime, ; Jabot & Pottier, ; Tilman, ), which has been observed in temperate forest understories (Baeten et al, ; Hedwall & Brunet, ). Second, this increase in light availability can accelerate effects of climate warming so that herbaceous communities come to resemble those of warmth‐adapted communities (Bjorkman et al, ; De Frenne et al, ; Helsen et al, ; Henn et al, ; Hoeppner & Dukes, ). The increasing light availability may also alter soil microbial communities and enhance their activity which can release nutrients for plants (Ma et al, ; Ni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The crucial question that emerges is, therefore, when and why is ITV more important? Previous studies have suggested that ITV is a mechanism by which plant species respond to local spatial resource heterogeneity (Valladares, Gianoli, & Gómez, 2007) and is related to environmental variation across the species' range (Helsen et al, 2017). Intraspecific trait variability may be particularly important in low diversity ecosystems where reduced competition could allow individuals of the same species to occupy a larger trait space (Freschet, Bellingham, Lyver, Bonner, & Wardle, 2013;Silvertown & Charlesworth, 2009;Violle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of inter- and intraspecific plant trait variation across environmental gradients, such as those related to latitude and elevation, have been receiving increasing attention (Anstett et al, 2018; Hahn et al, 2018; Pellissier, Roger, Bilat, & Rasmann, 2014; Woods et al, 2012). Although such studies are beyond doubt important and useful to test classic theories predicting herbivore defence (Anstett et al, 2015; Moles et al, 2011) and resource allocation patterns (Helsen et al, 2017; Kooyers, Greenlee, Colicchio, Oh, & Blackman, 2015), they also have to cope with the difficulty of potentially hidden dynamics along gradients. Changes in abiotic and biotic factors may be correlated and interconnected to changes in geographical location, which complicates the disentangling of environmental impacts on plant traits (Hahn et al, 2018; Johnson & Rasmann, 2011).…”
Section: Discussionmentioning
confidence: 99%